Epigenetic modification of MiR-429 promotes liver tumour-initiating cell properties by targeting Rb binding protein 4. Issue 1 (26th February 2014) - Li, Liang; Tang, Jing; Zhang, Baohua; Yang, Wen; LiuGao, Miyang; Wang, Ruoyu; Tan, Yexiong; Fan, Jianling; Chang, Yanxin; Fu, Jing; Jiang, Feng; Chen, Caiyang; et al.
Abstract : Objective: Liver tumour-initiating cells (T-ICs) are critical for hepatocarcinogenesis. However, the underlying mechanism regulating the function of liver T-ICs remains unclear. Methods: Tissue microarrays containing 242 hepatocellular carcinoma (HCC) samples were used for prognostic analysis. Magnetically activated cell sorting was used to isolate epithelial cell adhesion molecule (EPCAM)-positive cells. The gene expressions affected by miR-429 were determined by arrays. Co-immunoprecipitation was used to study interactions among retinoblastoma protein (RB1), Rb binding protein 4 (RBBP4) and E2F transcription factor 1 (E2F1). The DNA methylation status in CpG islands was detected by quantitative methylation analysis. miRNAs in microvesicles were isolated by a syringe filter system. Results: The significant prognosis factor miR-429 was upregulated in HCC tissues and also in primary liver T-ICs isolated from clinical samples. The enrichment of miR-429 in EPCAM + T-ICs contributed to hepatocyte self-renewal, malignant proliferation, chemoresistance and tumorigenicity . A novel functional axis involving miR-429, RBBP4, E2F1 and POU class 5 homeobox 1 (POU5F1 or OCT4) governing the regulation of liver EPCAM + T-ICs was established in vitro and in vivo. The molecular mechanism regulating miR-429 expression, involving four abnormal hypomethylated sites upstream of the miR-200b/miR-200a/miR-429 cluster, was first defined in both EPCAM + liver T-ICs and very early-stage HCC tissues. miR-429 secreted by high-expressing cells has the potential to become a proactive signalling molecule to mediate intercellular communication. Conclusions: Epigenetic modification of miR-429 can manipulate liver T-ICs by targeting the RBBP4/E2F1/OCT4 axis. This miRNA might be targeted to inactivate T-ICs, thus providing a novel strategy for HCC prevention and treatment.